An Augustinian Philosopher Between Dualism and Materialism: Ernan Mcmullin on Human Emergence: with Paul L. Allen, “An Augustinian Philosopher between Dualism and Materialism: Ernan McMullin on Human Emergence”; and Ernan McMullin, “Biology and the Theology of the Human” - Allen, Paul L. (Zygon, 2013)
In claiming the independence of theology from science, Ernan McMullin nevertheless saw the danger of separating these disciplines on questions of mutual significance, as his accompanying article “Biology and the Theology of the Human” in this edition of Zygon shows. This paper analyzes McMullin's adoption of emergence as a qualified endorsement of a view that avoids the excesses of both dualism and materialism. I argue that McMullin's distinctive contribution is the conceptual clarification of emergence in the light of a precise understanding of matter, in light of Aristotelian metaphysics and Darwinian theory. As applied to human nature, McMullin retains an Augustinian outlook that sees spirit as emergent in the human body and which posits a credible biblical hermeneutic. I indicate briefly how McMullin's perspective could be fortified by a fuller natural theology.